Pengaruh Profitabilitas, Likuiditas, Dan Ukuran Perusahaan Terhadap Opini Audit Going Concern Pada Perusahaan Retail Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Ade Indah Oktaviani; Mardiana Mardiana; Eduard Hotman Purba (IJAcc, 2024)
The purpose of this study is to determine the effect of Profitability (ROA), Liquidity (Current Ratio), and Company Size on Going Concern Audit Opinions on Retail Companies listed on the Indonesia Stock Exchange. The data used is secondary data derived from the financial statements of Retail Companies that have been published for the 2018-2022 period. Sampling using Purposive Sampling Technique which resulted in 33 Retail Companies. This research uses quantitative approach methods with data analysis methods used, namely descriptive statistics, logistic regression tests and Hypothesis Tests. The results of the study simultaneously Profitability, Liquidity, and Company Size affect the Going Concern Audit Opinion.